An Evaluation of the Need for Blood Transfusion When Using Patient Specific Instrumentation for Total Knee Arthroplasty - Myers, Kevin; Merwin, Sarah L.; Cabrera, Bryan; Lementowski, Peter (International Journal of Orthopedics and Rehabilitation, 2022)
The aim of this study was to compare the need for blood transfusion and other outcomes when using patientspecific instrumentation (PSI) versus traditional instrumentation. 45 patients underwent TKA with either PSI (12 unilateral/9 bilateral) or traditional instrumentation (19 unilateral/5 bilateral) using the same final implants. Use of PSI demonstrated shorter operative/ tourniquet times, and shorter length of stay compared to traditional TKA, but no difference in the need for blood transfusion. Post-hoc subgroup analysis demonstrated that bilateral PSI replacement had a significantly decreased need for blood transfusion, shorter length of stay, and shorter operative/tourniquet times than bilateral replacement with traditional instrumentation. Use of PSI resulted in shorter length of stay and shorter operative/tourniquet times, with bilateral PSI also having a decreased need for blood transfusion.